Porous Single‐Crystal Nitrides for Enhanced Pseudocapacitance and Stability in Energy Storage Applications - Xiangqi Gao; Guoliang Ma; Cong Luo; Shaobo Xi; Lingting Ye; Kui Xie (Advanced Science)
Abstract Supercapacitors have emerged as a prominent area of research in energy storage technology, primarily because of their high power density and notable stability compared to batteries. However, their practical implementation is hindered by their low energy densities and insufficient long‐term stability. In this study, bulk porous Nb4N5 and Ta3N5 single crystals with excellent pseudocapacitance and electrical conductivity are successfully prepared by solid‐phase transformation method. These monolithic porous single crystals (PSC) exhibit a long‐range ordered crystalline architecture and substantial specific surface area, which facilitate rapid charge transport and ion diffusion within the electrolyte‐permeated crystal lattice. Notably, the areal capacitance of the porous Nb4N5 single crystals is 12.9 F cm−2 at a current density of 6 mA cm−2 and 35.08 F cm−2 at a scan rate of 1 mV s−1. Furthermore, the energy density reached 1.79 mWh cm−2 at a power density of 20 mW cm−2, demonstrating their high energy storage capability. Moreover, these porous Nb4N5 single crystals exhibited robust capacitance retention and exceptional cycling stability, making them promising candidates for use as electrodes in energy storage applications. These results underscore the significant potential of porous metal nitride single crystals in advancing the field of capacitive energy storage.